Rates of return and early retirement disincentives: Evidence from a German pension reform - Holger Lüthen (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
To counteract the financial pressure emerging in aging societies, statutory pay-as-you-go pension schemes are undergoing fundamental reforms in many Western countries. Starting with cohort 1937, Germany introduced permanent pension deductions for early retirement. This paper examines the evolution of the profitability of pension contributions against the background of this reform for cohorts 1935-1945. I measure the profitability with the internal rate of return (IRR) and use high quality administrative data. For men the IRR declines from 2.4% to 1.2% and for women from 5.2% to 3.7%. The results suggest that the deductions introduced by the reform only cause some part of this trend. The majority of the trend, about 75%-80%, is caused by increased pension contributions.
Keywords: D02; D04; D14; D91; H55; 330; pensions; reform; early retirement; disincentives; pay-as-you-go; rates of return; Germany